2020
DOI: 10.1177/2320206820941365
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Dental Economics and Dental Healthcare Utilization in COVID-19: An Exploratory Study

Abstract: Aim: The current exploratory research establishes a correlation between the general unemployment rate due to COVID-19 and its effect on dental healthcare service utilization, workforce, and education attainments. Materials and methods: The conceptual model utilized in the study is the circular flow diagram explaining economy organization. The study is an exploratory research review. PRISMA guidelines are followed for the review of articles. The literature data for the current review study is obtained from Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Furthermore, U.S dental care spending has been projected to decline by up to 20 percent in 2021 (Nasseh & Vujicic, 2020). According to Patel (2020), actions like these would mean high unemployment rates among dental practices, that recruit dental assistants, dental hygienist, dentists, dental assistants, and other auxiliary staff. As seen in the study conducted by Khanal and Singh (2020), where some dentists reported of losing their job or receiving no salary.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, U.S dental care spending has been projected to decline by up to 20 percent in 2021 (Nasseh & Vujicic, 2020). According to Patel (2020), actions like these would mean high unemployment rates among dental practices, that recruit dental assistants, dental hygienist, dentists, dental assistants, and other auxiliary staff. As seen in the study conducted by Khanal and Singh (2020), where some dentists reported of losing their job or receiving no salary.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of the impacts on finance Goodell, 2020;Haroon & Rizvi, 2020;Phan & Narayan, 2020), researchers usually took the topics on stock, currency, financial system, gold and real estate trusts, insurance, and cryptocurrency, etc., in which the focus on stock market is the most, as stock is one of the most active financial indicators (Phan & Narayan, 2020). For the research about medical and health, many researchers discussed the economic challenges of COVID-19 on different medical departments, such as elective surgery (Best et al, 2020), dental surgery (Chamorro-Petronacci et al, 2020;Patel, 2020), etc. For human resources part, researchers' attention mainly focused on the employment situations and the general impacts and fluctuations in labor market (Kaur et al, 2020;Modrego et al, 2020;Webb et al, 2020).…”
Section: The Analyses Of the Pandemic's Economic Impacts On Different Industriesmentioning
confidence: 99%
“…These situations can lead to unpredictable longterm results such as unemployment. While the lockdowns and reductions in dental activities have a profound impact on the economy of this sector, all dental procedures during the Covid-19 outbreak should be continued with all precautions taken (32). An important consequence of this dramatic decrease in the number of treatments is that patients cannot have the necessary dental treatments, so there may be serious deterioration in oral and dental health, and advanced treatments require more costs.…”
Section: Since Our Study Was Conducted On Patients Who Applied To Karabük Oral and Dental Health Training And Researchmentioning
confidence: 99%